2022
DOI: 10.1111/jfpp.16666
|View full text |Cite
|
Sign up to set email alerts
|

Production of innovative antioxidant‐rich and gluten‐free extruded puffed breakfast cereals from purple sweet potato ( Ipomoea batatas L.) and red rice using a mixture design approach

Abstract: The effect of formulation on physiochemical and functional properties of extruded breakfast cereals was investigated. The anthocyanins of breakfast cereals were quantified using HPLC, and remarkable retention of anthocyanins and antioxidant properties was recorded. The purple sweet potato (PSP) indicated a most significant positive impact on antioxidant capacity, whereas the cornflour contributed toward a better expansion of the final product. The optimum formulation of breakfast cereal with an acceptable text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
1
3
0
Order By: Relevance
“…Under the optimum conditions used in the present work, a significant improvement in expansion was observed as compared to that of non-optimised samples, previously reported by the same research group (Senevirathna et al, 2022), as illustrated in Figures 2a and 2b. Furthermore, as shown in the scanning electron micrographs (Figure 2c and 2d), the optimised samples depicted a better cell structure, with smoother and thin cell walls than the nonoptimised samples.…”
Section: Appearance and Microstructure Of Optimised Breakfast Cerealsupporting
confidence: 76%
See 1 more Smart Citation
“…Under the optimum conditions used in the present work, a significant improvement in expansion was observed as compared to that of non-optimised samples, previously reported by the same research group (Senevirathna et al, 2022), as illustrated in Figures 2a and 2b. Furthermore, as shown in the scanning electron micrographs (Figure 2c and 2d), the optimised samples depicted a better cell structure, with smoother and thin cell walls than the nonoptimised samples.…”
Section: Appearance and Microstructure Of Optimised Breakfast Cerealsupporting
confidence: 76%
“…The PSPP and WRRF were stored at 4°C in laminated aluminium foil bags before use. The range of main ingredients used for the formulation of breakfast cereals were selected based on the optimised formulation, as reported in our previous work (Senevirathna et al, 2022). The dry ingredients were PSPP (55.00%), WRRF (15.00%), and CF (30.00%).…”
Section: Sample Preparationmentioning
confidence: 99%
“…Zhang, Sun, et al (2020) reported that eggplant peel was used in formulating a model food system in different thermal treatments. An innovative formulation of breakfast cereals was produced by combining purple sweet potato (PSP) and red rice, which contain a high amount of anthocyanins and antioxidants (Senevirathna et al, 2022). Furthermore, anthocyanins‐rich rice berries are used in the production of flavored yogurt using which also contributed to high total phenolic content, DPPH radical scavenging activity, and ferric reducing antioxidant power (FRAP) (Anuyahong et al, 2020).…”
Section: Anthocyaninsmentioning
confidence: 99%
“…For instance, Chinese steamed bread incorporating PSPF has exhibited enhanced color, polyphenol content, and antioxidant activity ( Cui & Zhu, 2022 ) Other studies have shown that PSPF can improve the structural properties of extruded rice products ( Wang et al, 2021 ). The extruded breakfast cereals made from whole red rice, corn flour, and PSPF possess superior cell structures with smoother and thinner cell walls compared to non-optimized samples ( Senevirathna, Ramli, Azman, & Juhari, 2023 ) Furthermore, incorporating 20% PSPF into refined wheat flour for noodles has been found acceptable to consumers, while also enriching their nutritional profile ( Uthai, Suktanarak, Chetyakamin, & Thumrongchote, 2022 ) Collectively, these findings underline the beneficial impacts of PSPF on product quality.…”
Section: Introductionmentioning
confidence: 97%